2019
DOI: 10.1177/1046496419865325
|View full text |Cite
|
Sign up to set email alerts
|

Linking Personality Trait Variance in Self-Managed Teams to Team Innovation

Abstract: Researchers have suggested that some personality traits are associated with better team functioning when team members are homogeneous, whereas other personality traits improve team functioning when team members are heterogeneous. This article extends these ideas to team innovation and examines (a) how team variance in extraversion, agreeableness, openness, and conscientiousness relates to innovation in teams; and (b) how these relationships dynamically evolve over time. Our study included 704 surveys completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 88 publications
(158 reference statements)
0
22
0
Order By: Relevance
“…Research on team composition showed that a higher proportion of collectivist-oriented team members predicted moderately higher perceived team cooperation (Eby & Dobbins, 1997). Besides, Den Hartog et al (2020) found a positive association of less variance in extraversion and conscientiousness with team innovation over time. The combination of minimal conscientiousness variance and maximized extraversion variance predicted the best short-term and long-term performance (Humphrey et al, 2011).…”
Section: Model Of Ksaos For Smt Performancementioning
confidence: 87%
See 1 more Smart Citation
“…Research on team composition showed that a higher proportion of collectivist-oriented team members predicted moderately higher perceived team cooperation (Eby & Dobbins, 1997). Besides, Den Hartog et al (2020) found a positive association of less variance in extraversion and conscientiousness with team innovation over time. The combination of minimal conscientiousness variance and maximized extraversion variance predicted the best short-term and long-term performance (Humphrey et al, 2011).…”
Section: Model Of Ksaos For Smt Performancementioning
confidence: 87%
“…However, the authors did not report the optimal share of conscientious members. Diversity regarding openness was unrelated to team innovation, although, interestingly, low variance in agreeableness was associated with lesser team innovation over time (Den Hartog et al, 2020). Team diversity in proactive behavior predicted worse teamwork behavior, and consequently less team proactive performance (Williams et al, 2010).…”
Section: Model Of Ksaos For Smt Performancementioning
confidence: 99%
“…As an initial research step, we chose not to alter the data’s information by any centering, but rather present it in accordance with its structure. Yet, an additional reason behind our decision to take such a course of action arose from disagreements between the different centering methods published by the various literature (Braun et al, 2020; den Hartog et al, 2020; English et al, 2004). The empty, or null, level model, describes the partition between variance at the student’s level and at the group-level.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, extraversion has been shown to be related to team processes such as stimulating discussion (Mohammed & Angell, 2003) or supportive behavior (Porter et al, 2003). In turn, there are findings indicating the advantage of homogeneous grouping in extraversion (den Hartog et al, 2020).…”
Section: Group Formation By Personality Traitsmentioning
confidence: 99%
“…I.e., the distinct person (their characteristics/traits etc) as opposed to the 'context' of individual is what is driving the adoption. This suggests the need for a return to trait theory alongside considering the role of network hubs in considering the adoption of innovation in service-based organisations(den Hartog et al, 2020;Davies et al, 2018).…”
mentioning
confidence: 99%